A Survey on collusion resistant data sharing in cloud environment - Rajkumar, N; Kannan, E (International Journal of Engineering and Technology, 2018)
Cloud Computing is an emerging technology that uses the internet and remote servers to save information and application. Cloud computing enables customers and organizations to utilize applications without establishment and access their own documents at any computer with internet access. Collusion Resistant Secured the way to deal the fulfillment of an abnormal state of security with complete protection. A large portion of these techniques depend on a presumption that semi-trusted and arrangement is absent. In this paper, we concentrate on the issue of conspiracies, in which a few gatherings may connive and share their record to find the private data of different gatherings. The other related works better than this is more secure. This paper reveals an overview and study of collusion resistance techniques in more secure and efficient way for data sharing in cloud storage.